Pelaksanaan Pembelajaran Daring pada Masa Pandemi Covid-19 di SDN 92 Kendari - Intan Indari; Jumarddin La Fua; Muhammad Ilham; Imaludin Agus; Raehang Raehang (IAIN Kendari, 2021)
This study attemps to analyze the implementation of online learning during the COVID-19 pandemic at SD Negeri 92 Kendari. This type of research is qualitative with observation, interviews and documentation as data collection methods. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results showed (1) Teachers at SD Negeri 92 Kendari used WhatsApp more in online learning during the covid-19 pandemic compared to the zoom meeting application and several other learning applications (2) the implementation of bold learning was carried out at the homes of each student who starting with the teacher opening greetings, followed by attendance, then the teacher sending the material in the form of pictures or videos through the WhatsApp group, then the teacher explained the material through voice notes and gave student assignments with the allotted time. (3) evaluation of bold activities is carried out to find out the progress and development of learning at home, as well as the success of students after carrying out the learning process during the covid-19 pandemic, then the results of the evaluation can be activated in improving student learning.Keywords: Online learning at Elementary School, Covid-19 Pandemic